2008
DOI: 10.2528/pierb08031225
|View full text |Cite
|
Sign up to set email alerts
|

Propagation of Waves in a Bifurcated Cylindrical Waveguide With Wall Impedance Discontinuity

Abstract: Abstract-In the present work the radiation of sound from a bifurcated circular waveguide formed by a semi-infinite rigid duct inserted axially into a larger infinite tube with discontinuous wall impedance is reconsidered through an alternative approach which consists of using the mode matching technique in conjunction with the Wiener-Hopf method. By expressing the total field in the appropriate waveguide region in terms of normal modes and using the Fourier transform technique elsewhere, we end up with a singl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…It was shown that the method of the effective non-Hermitian Hamiltonian can be used to calculate the S-matrix and the scattering function of sound-hard boundary acoustic scattering problem. Thanks to the projection of the total Hilbert space onto the inner states of the resonator the method is free of the discontinuity problem typical for the mode-matching techniques [29,30,31,32,33,34,35,36]. It was shown that in the continuous case the effective Hamiltonian can be truncated to a reasonable small number of eigenmodes of the closed system whose eigenfrequencies are concentrated around the frequency of the incident wave.…”
Section: Discussionmentioning
confidence: 99%
“…It was shown that the method of the effective non-Hermitian Hamiltonian can be used to calculate the S-matrix and the scattering function of sound-hard boundary acoustic scattering problem. Thanks to the projection of the total Hilbert space onto the inner states of the resonator the method is free of the discontinuity problem typical for the mode-matching techniques [29,30,31,32,33,34,35,36]. It was shown that in the continuous case the effective Hamiltonian can be truncated to a reasonable small number of eigenmodes of the closed system whose eigenfrequencies are concentrated around the frequency of the incident wave.…”
Section: Discussionmentioning
confidence: 99%
“…If a semi-infinite or finite geometry is in question, a hybrid method can be applied by using the Wiener-Hopf technique on the outer surface of the duct and the Mode-Matching method on the inner surface. 16,17 The Mode-Matching method is more suitable, especially for the discontinuities on the inner surface.…”
Section: Introductionmentioning
confidence: 99%
“…The contributions from the impedance discontinuities are accounted for through the solution of a Modified Wiener-Hopf Equation (MWHE) (Büyükaksoy et al, 2008;Tiryakioglu, Demir, 2016). Due to the difficulties in obtaining and solving the MWHE, the infinite lining is usually preferred rather than the finite one.…”
Section: Introductionmentioning
confidence: 99%